(untitled) (Academia Journal of Medicine, 2023)
In recent years, artificial intelligence (AI) has found its way into numerous industries, transforming the way we work and live. Dentistry is no exception, as AI powered technologies are revolutionizing the field, making it more efficient and enhancing patient care. One such breakthrough is the application of ChatGPT in dentistry. ChatGPT, powered by OpenAI, is a powerful language model that can comprehend and generate human-like responses, enabling dentists and their teams to leverage its potential in a multitude of ways. This article explores how ChatGPT is being applied in dentistry and the benefits it brings to both professionals and patients.